2012
DOI: 10.1002/app.38827
|View full text |Cite
|
Sign up to set email alerts
|

Film‐forming behavior and mechanical properties of colloidal silica/polymer latex blends with high silica load

Abstract: In this article, silica sol (diameter: 8–100 nm) and polymer latex (Tg < 25°C) were mixed and dried at room temperature to prepare nanocomposite films with high silica load (≥50 wt %). Effects of silica size, silica load, and the Tg of the polymer on the film‐forming behavior of the silica/polymer latex blend were investigated. The transparency, morphology, and mechanical properties of the nanocomposite films were examined by UV–Vis spectroscopy, SEM, and nanoindentation tests, respectively. Transparent and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It has been shown that silica-containing composites exhibit an increased elastic modulus 30 , yield stress 31 , hardness, and scratch resistance 32 . Conventional sol-gel methods for producing polymer/silica composites involve the use of tetraethoxysilane (TEOS) or tetramethoxysilane (TMOS), both of which are relatively expensive and can result in the release of volatile organic solvents (VOCs) 33 . A simple and greener alternative is the drying of latex blends containing colloidal silica.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that silica-containing composites exhibit an increased elastic modulus 30 , yield stress 31 , hardness, and scratch resistance 32 . Conventional sol-gel methods for producing polymer/silica composites involve the use of tetraethoxysilane (TEOS) or tetramethoxysilane (TMOS), both of which are relatively expensive and can result in the release of volatile organic solvents (VOCs) 33 . A simple and greener alternative is the drying of latex blends containing colloidal silica.…”
Section: Introductionmentioning
confidence: 99%
“…A simple and greener alternative is the drying of latex blends containing colloidal silica. Several publications focus on the creation of latex/silica nanocomposite films by drying latex dispersions containing silica 22,[33][34][35][36] . Martinez and Lewis, and Yang et al studied the film forming behaviour and mechanical properties of latex films containing colloidal silica particles 33,35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abrasion resistance performance was improved slightly for the polyacrylate/silica nanocomposite films with D 4 , which resulted from the outstanding wear and durability of silicon. However, the improvement was limited because polyacrylate/silica nanocomposite without D 4 already showed excellent abrasion resistance performance (mass loss 0.024 g) compared to the literature . There was not much potential to improve for the abrasion resistance performance even if D 4 was added to the system.…”
Section: Resultsmentioning
confidence: 96%
“…However, the improvement was limited because polyacrylate/ silica nanocomposite without D 4 already showed excellent abrasion resistance performance (mass loss 0.024 g) compared to the literature. 25,29 There was not much potential to improve for the abrasion resistance performance even if D 4 was added to the system. And the results confirmed the assumption.…”
Section: Resultsmentioning
confidence: 96%